Idolatry: A Reading Key for the Market Economy?. Issue 1 (March 2016) - Sung, Jung Mo
Abstract: This article proposes that theology can and must have a significant role in understanding current economic‐social reality. Using examples that portray the frequent use of religious terms among executives, economists, and political and social analysts, it shows that the discourse of the market system assumes a dogmatic faith in the market and that the theological concept of idolatry can be very useful in unveiling the system's fascination and sacrificial character.